Monetary policy and exchange rate regime of Malaysia - Ang, Michelle Qiu Yan (2011)
This paper aims to study the close interaction between exchange rate system and the operation of monetary policy, by investigating Malaysia’s economic performance in the various episodes relating to the happenings of major economic events – (1) before the peg;(2) during the peg; and (3) after the peg. Within those episodes, it questions if Malaysia was adopting interest rate as its operating tool for monetary policy, with specific reference to the United States (U.S.). It too highlights the coincidence of switch in exchange rate regime to a managed float between China and Malaysia.This paper aims to study the close interaction between exchange rate system and the operation of monetary policy, by investigating Malaysia’s economic performance in the various episodes relating to the happenings of major economic events – (1) before the peg;(2) during the peg; and (3) after the peg. Within those episodes, it questions if Malaysia was adopting interest rate as its operating tool for monetary policy, with specific reference to the United States (U.S.). It too highlights the coincidence of switch in exchange rate regime to a managed float between China and Malaysia.